2005
DOI: 10.1002/mds.20609
|View full text |Cite
|
Sign up to set email alerts
|

Burden of illness in Parkinson's disease

Abstract: This study quantifies direct medical care costs for individual patients with Parkinson's disease (PD) and projects total national costs of PD. Anonymous, patient-level data on health care utilization and cost were obtained from Medstat's MarketScan Research Databases. Patients were selected for study if they had either two instances of a diagnosis of PD or one diagnosis and two or more prescriptions for PD-related medication. A control group of persons without PD was selected for comparison. Total annual healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(182 citation statements)
references
References 13 publications
6
170
2
2
Order By: Relevance
“…Like schizophrenia, the economic burden of PD is high -a study comparing 20,000 PD patients to controls produced an estimated cost of $23 billion annually using data from 2002 [28] . Another study showed that PD is associated with large direct economic costs to society [29] .…”
Section: Psychosis In Parkinson's Diseasementioning
confidence: 99%
“…Like schizophrenia, the economic burden of PD is high -a study comparing 20,000 PD patients to controls produced an estimated cost of $23 billion annually using data from 2002 [28] . Another study showed that PD is associated with large direct economic costs to society [29] .…”
Section: Psychosis In Parkinson's Diseasementioning
confidence: 99%
“…The economic burden of PD is estimated to be $23 billion annually in US and projected to increase to $50 billion by year 2040 3. Current therapy is limited to symptomatic treatment; however, the disease continues to progress with accumulation of significant disability, worsening quality of life, reduced productivity, nursing home placement, and increased mortality 4. Attempts to slow or modify disease progression in PD have resulted in mixed outcomes and no treatment has yet to definitively demonstrate disease modification (see Table 1 for recent disease‐modifying trials) 5, 6, 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…This number is only to increase as the world population ages. 1 In addition to the increasing number of PD patients to be seen in neurology clinics for specialized care, the patients themselves also develop increasing needs at later stages of disease. Initially, patient care is usually focused on motor symptoms, including tremors, postural instability, gait, and rigidity.…”
Section: Introductionmentioning
confidence: 99%